Therapies for osteoarthritis today and tomorrow - review - Skrepnik, Nebojsa (Scripta Medica, 2020)
Osteoarthritis is a common human disease with well understood pathophysiology, signs and symptoms, prevalence, risk factors, pain, and suffering with great understanding of personal, economic and social effects around the world. There are no drugs or treatments considered “disease modifying”, with symptomatic control aiming to stave off the final solution of total joint replacement. Regenerative medicine and use of mesenchymal stem cells (MSC) promised hope to change that but have so far fallen short. This review focuses on current knowledge and use of MSC in clinic, completed research, and future directions for development of this once so promising biological treatment. Powerful treatment for pain in form of monoclonal antibodies against Nerve Growth Factor (NGF) are getting close to FDA approval in the US. Wnt signalling pathway modulators that decrease inflammation, increase function and potential to regenerate cartilage should be presented to the FDA early next year.
Keywords: Osteoarthritis; Mesenchymal stem cels; Wnt pathway; NGF antibodies